Relationships between motor impairments and activity limitations in patients with neuromuscular disorders. Issue 3 (23rd October 2008) - Vandervelde, L; Van den Bergh, P Y K; Renders, A; Goemans, N; Thonnard, J-L
Abstract : Aim: The strength and nature of the relationships between motor impairments and activity limitations assessed by the ACTIVLIM questionnaire were investigated in 245 patients with neuromuscular disorders. Methods: Measures of motor impairments consisted of: (1) a grip strength test using a Jamar dynamometer, (2) a Manual Muscle Testing bilaterally performed in 18 muscle groups and (3) a gait speed spontaneously adopted by the patients using the 10 m timed walking test. Results: Activity limitations were poorly correlated with grip strength in both hands (r = 0.3 and 0.36) and moderately correlated with gait speed (r = 0.53). Spearman's coefficients of correlation between the manual muscle testing and activity limitations were moderate to very poor (ρ = 0.5 to 0.17). Conclusion: The relationships between motor impairments and activity limitations are not straightforward in patients with neuromuscular disorders, indicating that the activity limitations should be separately assessed and cannot be simply inferred from motor impairment measures.